Nilai Pendidikan Dalam Novel Merahnya Merah Karya Iwan Simatupang: Pendekatan Sosiologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra Di Sma - Wicaksono, Ikhsan; , Dr. H. Nafron Hasjim (2016)
The purpose of this study is to describe the structure of the novel Merahnya Merah Iwan Simatupang, values education in the novel Merahnya Merah Iwan Simatupang, the implementation of the results of the research work of novel Merahnya Merah Iwan Simatupang for literature teaching materials in the secondary schools. The method used is descriptive qualitative. The object in this research is the educational values contained in the novel Merahnya Merah Iwan Simatupang. The data used in the form of sentences and paragraphs contained in the novel Merahnya Merah Iwan Simatupang. The primary data sources in the novel is a novel Merahnya Merah Iwan Simatupang, published by the PT. Gunung Agung, Jakarta in 1987, thick book 124 pages. Secondary data sources in this study is in the form of relevant articles. Engineering data collection using the technique references, refer to the technique, take note, interview, field transcript, and document. The validity of the data used is the triangulation theory and triangulation resources. Technique of data analysis in this study uses the data analysis techniques in dialectic. The results of the study based on structural analysis: themes in the novel Merahnya Merah is the life of a people battered by all the love and life problems. Homeless life experienced by the main character that is our character. The Groove that was used in the novel Merahnya Merah is the plot forward. The figures analysed was Tokoh Kita, Mr. Centeng, Maria, and Fifi. Setting the story in the novel Merahnya Merah background consists of a place, time, and social background. Educational value contained in the novel Merahnya Merah is the value of peace, the values of humility, honesty, responsibility, value is the value of love, and the value of cooperation. Implementation of Competency Standards and Basic Competence of the novel material can be seen in SK 7. understand the various tales, Indonesia novels or translations, and KD 7.2 that is analyzing the elements of intrinsic and extrinsic Indonesia novels or translations.